Nova expansão canavieira, mudanças espaciais e produtivas: o caso do município de Santa Rita – PB - Matias, Josias (2010)
The main objective of the research is to identify to the occurred changes in the space agrarian of the city of Rita Saint, during the last decades (1975-2009). The study the conception of the space developed for critical geography has as theoretical support, that is, the agreement of that the space is a social product. To reach the considered objective diverse methodological procedures had been used: ) the bibliographical research for the construction of the theoretical recital, for the reconstitution of the process of formation of the municipal agrarian space and to deepen aspects of the recent changes; b) the secondary research next to the governmental bodies, in particular next to the IBGE, and the entities of classroom, in view of the attainment of data to analyze the modifications in course; e c) direct research that understood visits of field for recognition of the studied reality, interviews with syndical, diligent leaderships and technician of the sucroalcooleiras companies. Use was made, also, of the photographic documentation of the searched space and the cartography. In such a way to have the dimension of the transformations of the canavieira activity in the recent period and its possible transformations in the space as in the relations established in the productive process, the recovery of the historical process of configuration of the agrarian space of Rita Saint was made, as well as the description of its natural elements. The accomplishment of the study sample that in the last few decades can be identified three distant phases: ) the period of expansion commanded for Proálcool (1975-1986), when a extensive growth of the system occurred; b) the period of crisis (1987-2000), when one verified a retraction of the canavieira activity and reduction of the production of sugar and the alcohol; e c) the current expansion characterized for the deepening of the technological intensity, for the improvement of the conditions of work, but keeping as characteristic basic the exploration of the work.